2021
DOI: 10.2196/24015
|View full text |Cite
|
Sign up to set email alerts
|

eHealth in Geriatric Rehabilitation: Systematic Review of Effectiveness, Feasibility, and Usability

Abstract: Background eHealth has the potential to improve outcomes such as physical activity or balance in older adults receiving geriatric rehabilitation. However, several challenges such as scarce evidence on effectiveness, feasibility, and usability hinder the successful implementation of eHealth in geriatric rehabilitation. Objective The aim of this systematic review was to assess evidence on the effectiveness, feasibility, and usability of eHealth interventi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 88 publications
1
36
0
Order By: Relevance
“…This may be an important fact for other researchers developing apps for multi-morbid older adults in rehabilitation facilities, who have rarely been involved in app development to this extent. Although studies on eHealth interventions are already being conducted in the context of geriatric rehabilitation, apps have only been considered as a form of intervention in a few studies to date, and many applications relate to specific clinical conditions, particularly in the neurological field [ 14 ]. In older adults with limited mobility and after hip fractures, positive effects on mobility, functional outcomes, and hospitalization could be achieved through telerehabilitation interventions with an app [ 16 ] or via web sites [ 15 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be an important fact for other researchers developing apps for multi-morbid older adults in rehabilitation facilities, who have rarely been involved in app development to this extent. Although studies on eHealth interventions are already being conducted in the context of geriatric rehabilitation, apps have only been considered as a form of intervention in a few studies to date, and many applications relate to specific clinical conditions, particularly in the neurological field [ 14 ]. In older adults with limited mobility and after hip fractures, positive effects on mobility, functional outcomes, and hospitalization could be achieved through telerehabilitation interventions with an app [ 16 ] or via web sites [ 15 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only 8% of all identified studies assessed the use of health apps as an eHealth intervention. However, the results on the applicability of eHealth with the target group indicated that interventions are feasible if adequate training takes place, and if the eHealth intervention is simple and has good usability [ 14 ]. For example, a study on telerehabilitation via a website compared with conventional rehabilitation after a hip fracture showed that patients in the telerehabilitation group achieved better functional scores than those in the control group [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, older adults may have minimal experience and familiarity with technology, and their chronic condition may also affect the usability of digital technology for self-care. It has emerged that the main difficulties of the elderly to use digital technology were due to vision and hearing issues [ 50 ].…”
Section: Advancing Self-care Through Technologymentioning
confidence: 99%
“…The combination of subjective symptoms and other objective findings may contribute to personalized patient care and can be used in the preventive setting, at diagnosis, during treatment, rehabilitation, follow-up or in the palliative setting, 8 so as to realize activity monitoring and self-management, health care education, home care or symptom monitoring. At the same time, in the field of Gerontology, 9 it allowed rehabilitation in virtual space or serious games or the development of intelligent framework. 10 , 11 The current coronavirus disease 2019 (COVID-19) pandemic highlighted some potential of eHealth, which could not only help overcome COVID-19, but also improve many aspects of health care, 12 including cancer care.…”
Section: Introductionmentioning
confidence: 99%